High light stress under phosphorus limitation in summer may accelerate diatom shift from Skeletonema to Chaetoceros in an oligotrophic coastal area of Japan - Yano, Ryoko; Ohara, Shizuka; Koike, Kazuhiko (Frontiers in Marine Science, 2023)
In the Seto Inland Sea, the largest semi-enclosed sea in Japan, the most dominant diatom in the past, Skeletonema spp., has been replaced by another diatom Chaetoceros spp. since the 1980s, and this shift is often explained as the result of oligotrophication. Based on previous observations of a shift from Skeletonema spp. to Chaetoceros spp. under prolonged sunny conditions, the recent increase in solar insolation over the last 30 years might have also accelerated the replacement of Skeletonema by Chaetoceros, especially during the summer when nutrient levels are relatively low and solar insolation is high. In our experiments, culture strains of Skeletonema costatum and Chaetoceros lorenzianus under severely nitrogen-limited conditions exhibited less non-photochemical quenching (NPQ) under prolonged exposure (1 h) to high light (800 µmol-photons m-2 s-1) and a decrease in photochemical quenching (qP) which was especially notable in S. costatum. Conversely, marked increases in NPQ were observed under severely phosphorus-limited conditions, even under short time exposure (30 s) to high light, even though the increase in NPQ could not relieve the decrease in qP, which was more apparent in S. costatum. These trends in NPQ and qP were attributed to the limited nutrients because replenishment of the nutrients led to a decrease in NPQ and an increase in qP. Interestingly, this recovery was faster in C. lorenzianus than S. costatum. The results showed that phosphorus depletion caused severe photoinhibition especially in S. costatum, irrespective of active NPQ induction. Further, given the severe phosphorus-limited conditions in the Seto Inland Sea for an extended period, we conducted competition experiments using continuous coculture of both species to simulate the typical summer environment where severe phosphorus limitation and high light occur. The results showed that the shift from S. costatum to C. lorenzianus was accelerated by continuous exposure to high light, which could explain the recent shift in the dominant species in the summer in the study area.